2011
DOI: 10.1093/hmg/ddr282
|View full text |Cite
|
Sign up to set email alerts
|

Ccdc66 null mutation causes retinal degeneration and dysfunction

Abstract: Retinitis pigmentosa (RP) is a group of human retinal disorders, with more than 100 genes involved in retinal degeneration. Canine and murine models are useful for investigating human RP based on known, naturally occurring mutations. In Schapendoes dogs, for example, a mutation in the CCDC66 gene has been shown to cause autosomal recessively inherited, generalized progressive retinal atrophy (gPRA), the canine counterpart to RP. Here, a novel mouse model with a disrupted Ccdc66 gene was investigated to reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 25 publications
3
53
0
Order By: Relevance
“…CCDC66 point mutation in dogs and null mutations in mouse were previously implicated in retinal degeneration, a phenotype that is common to ciliopathies (Dekomien et al, 2010;Gerding et al, 2011). We first identified CCDC66 as a proximity partner for known centriolar satellite proteins including CEP72, which interacts with CEP290 and functions in cilium formation and ciliary targeting of the BBSome complex (Stowe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CCDC66 point mutation in dogs and null mutations in mouse were previously implicated in retinal degeneration, a phenotype that is common to ciliopathies (Dekomien et al, 2010;Gerding et al, 2011). We first identified CCDC66 as a proximity partner for known centriolar satellite proteins including CEP72, which interacts with CEP290 and functions in cilium formation and ciliary targeting of the BBSome complex (Stowe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Given the possible role of CCDC66 in ciliary trafficking, perturbation of this function could lead to photoreceptor degeneration through mislocalization of proteins required for phototransduction. Previous studies reported localization of CCDC66 to the inner segments of photoreceptor cells (Dekomien et al, 2010) and to the outer segment of rod cells (Gerding et al, 2011). Higher resolution localization studies in photoreceptor cells are required to determine whether the localization of to the centrosome and cilium complex and/or microtubules in RPE1 cells reflects localization in photoreceptor cells.…”
Section: Research Articlementioning
confidence: 99%
See 3 more Smart Citations